2011
DOI: 10.5194/bg-8-2815-2011
|View full text |Cite
|
Sign up to set email alerts
|

Eddy covariance flux measurements confirm extreme CH<sub>4</sub> emissions from a Swiss hydropower reservoir and resolve their short-term variability

Abstract: Abstract. Greenhouse gas budgets quantified via landsurface eddy covariance (EC) flux sites differ significantly from those obtained via inverse modeling. A possible reason for the discrepancy between methods may be our gap in quantitative knowledge of methane (CH 4 ) fluxes. In this study we carried out EC flux measurements during two intensive campaigns in summer 2008 to quantify methane flux from a hydropower reservoir and link its temporal variability to environmental driving forces: water temperature and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 51 publications
6
79
1
Order By: Relevance
“…While proving the feasibility of EC measurements in freshwater ecosystems, aquatic EC work also highlights challenges related to the application of this terrestrially optimized approach to aquatic systems (Vesala et al, 2006;Eugster et al, 2011). Overall, EC shows great promise with respect to the following: (1) integration of all gas flux pathways from the lake sediments to the atmosphere; (2) continuous flux monitoring over time, enabling the capture of episodic ebullition events of CH 4 in lakes (Eugster et al, 2011); and (3) the analysis of dynamic responses of lake-atmosphere carbon fluxes to temporal (including diurnal) changes in environmental variables (Eugster, 2003;Vesala et al, 2006;Podgrajsek et al, 2014b).…”
Section: Scale and Distribution Of Ghg Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…While proving the feasibility of EC measurements in freshwater ecosystems, aquatic EC work also highlights challenges related to the application of this terrestrially optimized approach to aquatic systems (Vesala et al, 2006;Eugster et al, 2011). Overall, EC shows great promise with respect to the following: (1) integration of all gas flux pathways from the lake sediments to the atmosphere; (2) continuous flux monitoring over time, enabling the capture of episodic ebullition events of CH 4 in lakes (Eugster et al, 2011); and (3) the analysis of dynamic responses of lake-atmosphere carbon fluxes to temporal (including diurnal) changes in environmental variables (Eugster, 2003;Vesala et al, 2006;Podgrajsek et al, 2014b).…”
Section: Scale and Distribution Of Ghg Measurementsmentioning
confidence: 99%
“…Overall, EC shows great promise with respect to the following: (1) integration of all gas flux pathways from the lake sediments to the atmosphere; (2) continuous flux monitoring over time, enabling the capture of episodic ebullition events of CH 4 in lakes (Eugster et al, 2011); and (3) the analysis of dynamic responses of lake-atmosphere carbon fluxes to temporal (including diurnal) changes in environmental variables (Eugster, 2003;Vesala et al, 2006;Podgrajsek et al, 2014b). A significant portion of gaseous carbon emissions from seasonally ice-covered lakes appears to occur during spring ice-thaw (e.g.…”
Section: Scale and Distribution Of Ghg Measurementsmentioning
confidence: 99%
“…The component drivers respond differently to slow and fast changes in meteorological covariates (Baldocchi et al, 2001;Koebsch et al, 2015) such that different mechanisms may explain the diel and seasonal variability of the flux. For example, temperature affects emissions through convective mixing on short timescales and through the rate of sediment methanogenesis on longer timescales; the diurnal cycle of insolation may have a limited effect on production because the heat capacity of the water buffers the temperature signal (Fang and Stefan, 1996). Similar phase lags and amplifications may lead to hysteretic flux patterns, such as cold season emission peaks due to release of gases from the hypolimnion in dimictic lakes (Encinas Fernández et al, 2014;López Bellido et al, 2009) or thermal inertia of lake sediments (Zimov et al, 1997).…”
Section: Drivers Of Diffusive Ch 4 Emissionsmentioning
confidence: 99%
“…The water column is generally well-mixed and permanently oxygenated [DelSontro et al, 2010]. Studies based on gas traps, mass balance calculations and eddy covariance showed that CH 4 emission from Lake Wohlen to the atmosphere was the highest ever documented for a temperate reservoir, and mainly attributable to ebullition [DelSontro et al, 2010;Eugster et al, 2011].…”
Section: Site Descriptionmentioning
confidence: 99%